2008
DOI: 10.1111/j.1467-9353.2007.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Sales at Farmers' Markets: An Iowa Study

Abstract: The 180 farmers' markets operating in a range of urban to rural communities in Iowa provide a useful setting to evaluate factors affecting sales at these markets. Higher average sales at markets tended to be associated with urban and higher income areas. Only 30% of vendors reported sales greater than $5,000, mostly in the produce category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 4 publications
4
49
0
Order By: Relevance
“…Similar to the present study, several studies concluded that the average FM customer was over 40 years of age, although Velasquez et al found an average customer age of 34 years [19][20][21]25,31]. It is possible that older community members use FM for social reasons in addition to health-consciousness, since Hunt's review found that increased age was significantly related to more frequent social interactions [32].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar to the present study, several studies concluded that the average FM customer was over 40 years of age, although Velasquez et al found an average customer age of 34 years [19][20][21]25,31]. It is possible that older community members use FM for social reasons in addition to health-consciousness, since Hunt's review found that increased age was significantly related to more frequent social interactions [32].…”
Section: Discussionsupporting
confidence: 72%
“…Other on-site surveys confirmed these findings, with 60% to 94% of respondents attaining at least some level of college education [20,21,26,33]. However, Varner and Otto found no significant differences in sales at FM where educational attainment was lower than the surrounding US Census area [31]. Therefore, research is needed to better understand divergent findings about the education of farmers' market shoppers.…”
Section: Discussionmentioning
confidence: 68%
“…We also provided a paper version of the questionnaire to reduce the bias of the sample inherent to this selection method. The validity concept of our selection was based on the demographic characteristics of consumers frequently shopping at markets (Henneberry and Agustini, 2004;McGarry Wolf et al, 2005;Varner and Otto, 2008), which are quite similar to that of Hungarian Internet users (NRC Piackutató, 2011): educated, above-average status, higher income, urban population. We received 1029 questionnaires (78 on paper and 951 on-line), of which 851 were validly completed.…”
Section: Methodology Sampling Methodsmentioning
confidence: 99%
“…By contrast, in the literature, product quality is generally described through multiple attributes without distinction. It has been posited to influence patronage decisions directly (i.e., [18][19][20]). In our study, the consequence 'quality product' was perceived as being 'nutritous' and 'delicious'.…”
Section: Discussionmentioning
confidence: 99%